Target ratcheting and effort reduction - Bouwens, Jan; Kroos, Peter (Journal of Accounting and Economics, 2011)
In this paper, we examine how retail store managers reduce their sales activity in response to target ratcheting. We find that managers with favorable sales performance in the first three quarters reduce their sales activity in the final quarter. We also document that managers who engage in sales reducing activities enhance their likelihood of meeting their next-year sales target, which is based on their current sales. That is, managers who reduce their sales activity in the final quarter are more likely to beat their next-year sales targets than managers who refrain from reducing their final-quarter sales.